2021
DOI: 10.3390/ijerph18094908
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Toxoplasma gondii IgG and Cardiovascular Biomarkers

Abstract: Background: Toxoplasma gondii (T. gondii) is a protozoan parasite with high prevalence worldwide. More than 40 million individuals in the United States carry this parasite. T. gondii infection causes toxoplasmosis, which is the leading cause of death associated with foodborne diseases in the United States. T. gondii infects humans through different routes, and it is capable of invading a wide range of tissues in the human body following the infection. Methods: The main objective of this study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The exposure to environmental contaminants is rarely isolated. Most human beings are exposed to a complex mixture of many environmental [ 57 , 58 ] and social exposures [ 59 , 60 ], and the physiological manifestation of them determines the biological response both in the short and long term. The exposome embodies this concept and reflects the reality of how exposure occurs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to environmental contaminants is rarely isolated. Most human beings are exposed to a complex mixture of many environmental [ 57 , 58 ] and social exposures [ 59 , 60 ], and the physiological manifestation of them determines the biological response both in the short and long term. The exposome embodies this concept and reflects the reality of how exposure occurs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pathogenicity of toxoplasmosis is linked to an increase in oxidative stress and inflammation; thus, it is associated with various diseases such as heart diseases, obsessivecompulsive disorder, and schizophrenia [11][12][13]. Moreover, Babekir et al [14] indicated that T. gondii seropositivity is associated with elevated levels of biomarkers and clinical markers such as triglycerides (TG), systolic blood pressure (SBP), low-density lipoprotein cholesterol (LDL), gamma-glutamyl transferase (GGT), and C-reactive protein (CRP).…”
mentioning
confidence: 99%
“…Furthermore, a positive association between Toxoplasma and AST ( p = 0.0211), ALT ( p = 0.0221), and GGT ( p = 0.0258) was revealed after adjusting for BMI, age, gender, and race. Prior studies linked T. gondii IgG+ and adverse levels of several clinical biomarkers related to heart and kidney function, including blood pressure, TG, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, albuminuria, and GGT [ 15 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional variables considered in the analysis were gender, age, race/ethnicity, and occupation (longest job). The occupation variable had 22 levels (types of occupations) which we grouped into two groups: group 1 included the occupations which were found to be associated with Toxoplasma infection in previous studies [ 14 , 22 , 50 ] and group 2 included all other types of occupations. Specifically,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation